Grass maturity effects on cattle fed silage-based diets 2. Cell wall digestibility, digestion and passage kinetics - Rinne, Marketta; Huhtanen, Pekka; Jaakkola, Seija (Elsevier, 1997)
Abstract Four silages were harvested at approximately 1-week intervals from the same timothy--meadow fescue sward and studied in a 4×4 Latin square experiment with four ruminally and duodenally cannulated young cattle. The diets comprised silage and concentrate (7:3 dry matter (DM) basis) and were fed at a rate of 70 g DM kg-0.75 liveweight in two equal meals per day. Neutral detergent fibre (NDF) digestibility was 0.757, 0.765, 0.692 and 0.686 on diets based on the four silages in order of harvest date. Increasing maturity of grass ensiled showed linear (PL<0.001) and cubic (PC<0.01) trends. NDF was separated into digestible (DNDF) and indigestible (INDF) fractions, which differed clearly in their rate of passage from the rumen (on average 0.0141 vs. 0.0258 h-1). The rate of digestion (kd) of DNDF was on average 0.076 h-1 when derived from the rumen evacuations but only 0.036 h-1 when calculated from the disappearance from nylon bags incubated in the rumen. Both methods detected decreased kd of NDF with increasing maturity of grass ensiled. Rate of passage from the rumen increased with increasing maturity of grass both when determined for NDF with rumen evacuation technique and from the faecal excretion of ytterbium calculated with a two-pool model. Mean retention time (MRT) in the non-escapable pool of particles increased (PL<0.01) with increasing grass maturity, the opposite being true for the escapable pool (PL<0.05), resulting in no change in the total ruminal MRT. Pool sizes of ruminal DM (PL<0.01) and NDF (PL<0.001) increased with increasing maturity of grass. Ruminal NDF digestibility was caly different methods. When digestion kineetic parameters were derived from rumen evacuations and two-pool models used for passage kinetics, estimated digestibilities were very close to the observed ones.
Keywords: Ko; korjuuaikapalvelu; nauta; nurmirehut; korjuuaste; sulavuus; ravitsemusfysiologia; ruokinta; märehtijät; grass maturity; cell wall; digestion; passage; kinetics; ruminant